Accurate quantitative wide-field fluorescence microscopy of 3-D spheroids. (November 2016) - Leary, Elizabeth; Rhee, Claire; Wilks, Benjamin; Morgan, Jeffrey R.
Hundreds of commercially available fluorescent dyes are used to quantify a wide range of biological functions of cells in culture, and their use has been a mainstay of basic research, toxicity testing, and drug discovery. However, nearly all of these dyes have been optimized for use on cells cultured as two-dimensional monolayers. Three-dimensional culture systems more accurately recapitulate native tissues, but their size and complexity present a new set of challenges for the use of fluorescent dyes, especially with regards to accurate quantitation. We determined the most accurate method to quantify fluorescence as a function of whether cells were uniformly labeled with dye prior to spheroid formation or if the dye was diffused into the spheroid after its formation. Using multicellular spheroids labeled with calcein-AM via these two different staining methods, we performed time-lapse fluorescence microscopy. For uniformly labeled spheroids, fluorescence was best normalized to volume, whereas for spheroids labeled via dye diffusion, fluorescence was best normalized to surface area. This framework for evaluating dyes can easily be extended to other applications. Utilizing the appropriate size-based normalization strategy enhanced our ability to detect statistically significant differences between experimental conditions.